Comparing acute versus AIDS ART initiation on HIV-1 integration sites and clonal expansion - Jun Wang; Nan Xiao; Zhengnong Zhu; Haiyan Qiao; Fang Zhao; Lukun Zhang; Jizhou Gou; Mengji Lu; Yun He; Hongzhou Lu; Qian Li (Signal Transduction and Targeted Therapy)
Abstract Early antiretroviral therapy (ART) initiation is known to limit the establishment of the HIV reservoir, with studies suggesting benefits such as a reduced number of infected cells and a smaller latent reservoir. However, the long-term impact of early ART initiation on the dynamics of the infected cell pool remains unclear, and clinical evidence directly comparing proviral integration site counts between early and late ART initiation is limited. In this study, we used Linear Target Amplification-PCR (LTA-PCR) and Next Generation Sequencing to compare unique integration site (UIS) clonal counts between individuals who initiated ART during acute HIV infection stage (Acute-ART group) and those in the AIDS stage (AIDS-ART group). Our analysis revealed distinct clonal distribution patterns, with greater UIS heterogeneity in Acute-ART group and more homogeneity in AIDS-ART group. Monoclonal UIS accumulation, predominantly in-gene regions, was influenced by ART timing and duration, with early treatment delaying this process. Host cell genes integrated by HIV provirus as monoclonal types were enriched in cell cycle and lymphocyte activation pathways. Tumor suppressor genes (TSGs) were more frequently integrated as monoclonal types in AIDS-ART group, suggesting potential risk factors. Overall, we introduced a sequencing method to assess provirus size in human peripheral blood and identified the widespread presence of monoclonal distribution of UIS in AIDS-ART group after long-term treatment. The early intervention helps slow the progress of clonal expansion of infected cells, reducing the formation of stable and persistent reservoirs, and ultimately posing fewer barriers to achieving a functional cure.